TPU foamed film with stereoscopic texture not deformed after multiple heat pressing and preparation method thereof
Patent Information
- Application Number
- CN202510561693.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-04-30
AI Technical Summary
现有的TPU发泡膜为了满足消费者的需求,凸显出膜层的立体感,在TPU发泡层表面形成凹凸不平的纹理层,然而大多纹理层在使用过程中不耐磨、不耐曲折,且在生产工艺中经多次热压后材料表面纹理发生形变,失去纹理效果
[0032]本发明TPU发泡膜的制备方法工艺简单,操作易控,有利于工业化大生产,制得的TPU发泡膜质量稳定,且纹理层多次热压后立体纹路不变形,即纹理层具有优异的耐磨性同时,也具有良好的附着力、耐老化性以及耐热性,使得TPU发泡膜具有具有优异的耐磨性同时,也具有良好的耐老化性以及优异的耐热性能,综合性能优越。
Smart Images

Figure CN120287703B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of TPU technology, specifically to a TPU foam film whose three-dimensional texture does not deform after multiple hot pressings and its preparation method. Background Technology
[0002] TPU foam film has been widely used due to its lightweight, softness, good elasticity, and excellent mechanical properties. It can be applied to various fabrics and other products, including clothing, tents, footwear, and automotive interiors. To meet consumer demand and enhance the three-dimensional effect of the film layer, existing TPU foam films often feature an uneven textured layer on the surface. However, most of these textured layers are not wear-resistant or flexurally resistant during use, and the surface texture deforms and loses its effect after repeated hot pressing during the manufacturing process. Summary of the Invention
[0003] In order to overcome the shortcomings and deficiencies of the existing technology, the purpose of this invention is to provide a TPU foam film whose three-dimensional texture does not deform after multiple hot pressings. This TPU foam film has excellent wear resistance, good adhesion, UV aging resistance and heat resistance, is easy to use and has a wide range of applications.
[0004] The present invention provides a simple and easy-to-control method for preparing a TPU foam film with a three-dimensional texture that does not deform after multiple hot pressings. It has a low defect rate, good economic benefits, and is conducive to large-scale industrial production. The TPU foam film obtained has stable quality, and its textured layer does not deform after multiple hot pressings. That is, the TPU foam film has excellent wear resistance, as well as good adhesion, UV aging resistance, heat resistance, flexural resistance, and superior comprehensive performance.
[0005] The objective of this invention is achieved through the following technical solution: a TPU foam film with a three-dimensional texture that does not deform after multiple hot pressings, comprising a texture layer and a TPU foam layer, wherein the texture layer is disposed on the upper surface of the TPU foam layer, and the upper surface of the TPU foam layer has multiple grooves arranged in a matrix, wherein the cross-section of the grooves is an inverted trapezoid, and the lower end of the texture layer extends into the grooves with an insert block, wherein the insert block engages with the grooves.
[0006] Furthermore, the groove has a depth of 25-35 μm, and the distance between two adjacent grooves is 95-105 μm. The top width of the groove cross-section is 45-55 μm, and the bottom width is 25-35 μm.
[0007] Furthermore, the thickness of the textured layer is 80-100μm; the thickness of the TPU foam layer is 0.4-1.2cm.
[0008] Furthermore, the textured layer is coated with a composite PU coating.
[0009] The TPU foam film of this invention, which maintains its three-dimensional texture even after multiple hot pressings, has an ingenious structure. A groove with an inverted trapezoidal cross-section is provided on the surface of the TPU foam layer. An insert extends from the lower end of the textured layer into the groove, allowing the composite PU coating to penetrate and solidify within the groove. The groove and the insert form a "rivet"-like mechanical interlocking structure, enhancing mechanical interlocking and ensuring a stable connection between the TPU foam layer and the textured layer. This prevents delamination of the TPU foam layer and textured layer after two hot pressings during the production process. The textured layer exhibits excellent adhesion and heat resistance, highlighting the three-dimensional effect of the product.
[0010] Furthermore, the preparation method of the composite PU coating includes the following steps:
[0011] A1. Place the diol in a reaction vessel, stir and heat to 115-130℃, control the pressure in the reaction vessel to -0.02-0.06MPa, and dehydrate; then purge with nitrogen, cool to 75-85℃, add isophorone diisocyanate and catalyst, catalyze the reaction for 1-3 hours, cool to 65-75℃, add 1-(furan-2-yl)-neopentane-1,3-diol for chain extension reaction for 1-2 hours, then add methyl ethyl ketone oxime for end-capping reaction for 1-2 hours. Once the reaction is complete, mixture one is obtained.
[0012] A2. Raise the temperature to 70-80℃, add silica sol and alumina nanoparticles to mixture one, stir evenly, and sonicate for 1-2 hours to obtain mixture two.
[0013] A3. Cool to room temperature, add bismaleimide and epoxy resin to mixture two and stir until homogeneous to obtain composite PU coating.
[0014] Furthermore, the molar ratio of the diol, 1-(furan-2-yl)-neopentane-1,3-diol, methyl ethyl ketone oxime and isophorone diisocyanate is 1:0.4-0.8:0.2-0.6:1-2.
[0015] Furthermore, the diol is at least one of polycaprolactone diol, polytetrahydrofuran diol, and polypropylene oxide diol.
[0016] Furthermore, the molar ratio of the bismaleimide to 1-(furan-2-yl)-neopentane-1,3-diol is 1:2.2-2.5.
[0017] Furthermore, the amount of epoxy resin added is 15-25% of the total mass of the diol, 1-(furan-2-yl)-neopentane-1,3-diol, methyl ethyl ketone oxime and isophorone diisocyanate.
[0018] Furthermore, the epoxy resin used is a bisphenol A type epoxy resin with an epoxy value of 0.46 from Shanghai Luohe High-Tech Materials Co., Ltd.
[0019] Furthermore, the total amount of silica sol and alumina nanoparticles added is 8-16% of the total mass of diol, 1-(furan-2-yl)-neopentane-1,3-diol, methyl ethyl ketone oxime and isophorone diisocyanate, and the mass ratio of silica sol to alumina nanoparticles is 1:0.3-0.7.
[0020] Furthermore, the alumina nanoparticles have a particle size of 50-100 nm.
[0021] Furthermore, the preparation method of the silica sol includes the following steps: preparing tetraethyl orthosilicate, deionized water and anhydrous ethanol in a molar ratio of 1:3.8-4.2:3.8-4.2, adjusting the pH value to 1-2 with concentrated hydrochloric acid, and stirring at 280-320 r / min for 25-40 min at 30-40℃ to obtain silica sol.
[0022] Furthermore, the catalyst is at least one selected from dibutyltin dilaurate and stannous octoate. The amount of catalyst added is 0.03-0.05% of the total mass of the diol, 1-(furan-2-yl)-neopent-1,3-diol, methyl ethyl ketone oxime, and isophorone diisocyanate.
[0023] Furthermore, the TPU foam film also includes a TPU hot melt adhesive film and a non-woven fabric, which are sequentially bonded to the lower surface of the TPU foam layer from top to bottom.
[0024] Furthermore, the thickness of the TPU hot melt adhesive film is 0.08-0.1cm, and the thickness of the nonwoven fabric is 0.2-0.4cm.
[0025] The present invention also provides a method for preparing a TPU foam film with non-deformable three-dimensional texture after multiple hot pressing, comprising the following steps:
[0026] S1. Take the TPU foam layer, carve grooves on the upper surface of the TPU foam layer using an ultraviolet laser engraving machine, then place it in a processing chamber and introduce nitrogen gas, and use plasma equipment to perform plasma surface activation on the upper surface of the TPU foam layer.
[0027] S2. Under nitrogen protection, the composite PU coating is applied to the upper surface of the activated TPU foam layer to form a composite PU layer. The composite PU layer is hot-pressed at a temperature of 130-150℃ for 30-60 seconds using a mold and then rapidly cooled to room temperature at a pressure of 12-17 MPa, so that an uneven texture is formed on the upper surface of the composite PU layer, forming a textured layer.
[0028] S3. Take TPU hot melt adhesive film and non-woven fabric, and attach the TPU hot melt adhesive film and non-woven fabric to the lower surface of the TPU foam layer from top to bottom. Use a mold to hot press it at a temperature of 90-110℃ for 10-30 seconds, and then quickly cool it to room temperature at a pressure of 0.5-1Mpa. This allows the TPU hot melt adhesive film to melt and firmly bond the TPU foam layer and non-woven fabric together to obtain a TPU foam film.
[0029] Furthermore, in step S1, the ultraviolet laser engraving machine uses an ultraviolet light wavelength of 350-360nm, the plasma processing power is 80-130W, the pressure is 10-50Pa, and the processing time is 90-150s.
[0030] Furthermore, the TPU foam layer uses TPU foam film of model ZD-85A from Guangdong Zhongding Technology Development Co., Ltd., with a thickness of 0.4-1.2cm and a density of 0.3g / cm³. 3 .
[0031] Furthermore, the textured layer does not deform after hot pressing.
[0032] The preparation method of the TPU foam film of this invention is simple and easy to control, which is conducive to large-scale industrial production. The TPU foam film obtained is of stable quality, and the three-dimensional texture does not deform after multiple hot pressings. That is, the texture layer has excellent wear resistance, as well as good adhesion, aging resistance and heat resistance. This makes the TPU foam film have excellent wear resistance, good aging resistance and excellent heat resistance, with superior overall performance.
[0033] The beneficial effects of this invention are as follows: The TPU foam film structure that does not deform after multiple hot pressings is ingenious. A groove with an inverted trapezoidal cross-section is provided on the surface of the TPU foam layer. An insert extends from the lower end of the textured layer into the groove, allowing the composite PU coating to penetrate and solidify into the insert. The groove and the insert form a "rivet"-like mechanical interlocking structure, enhancing mechanical interlocking and ensuring a stable connection between the TPU foam layer and the textured layer. This prevents the TPU foam layer from delaminating from the textured layer after two hot pressings during the production process. Furthermore, the textured layer is coated with a composite PU coating, and its three-dimensional texture remains unchanged after multiple hot pressings. This results in excellent wear resistance, good adhesion, aging resistance, and heat resistance, highlighting the three-dimensional effect of the product. Simultaneously, the TPU foam layer helps improve the film's elasticity and impact resistance, resulting in a TPU foam film with stable quality, good shape retention, excellent shape stability, and superior wear resistance, aging resistance, and heat resistance after multiple hot pressings. The preparation method of TPU foam film is simple, easy to operate and control, with low defect rate, high output and good economic benefits, which is conducive to large-scale industrial production. Attached Figure Description
[0034] Figure 1 This is a schematic diagram of the structure of Embodiment 1 of the present invention;
[0035] Figure 2 This is an exploded structural diagram of Embodiment 1 of the present invention;
[0036] Figure 3 This is an exploded structural diagram of Embodiment 2 of the present invention.
[0037] The attached figures are labeled as follows:
[0038] 1. Textured layer; 2. TPU foam layer; 3. Groove; 4. Insert; 5. TPU hot melt adhesive film; 6. Non-woven fabric. Detailed Implementation
[0039] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments. The content mentioned in the embodiments is not intended to limit the present invention.
[0040] Example 1
[0041] In this embodiment, a TPU foam film with a three-dimensional texture that does not deform after multiple hot pressings includes a textured layer and a TPU foam layer. The textured layer is disposed on the upper surface of the TPU foam layer. Multiple grooves are formed on the upper surface of the TPU foam layer. The multiple grooves are distributed in a matrix. The cross-section of the groove is an inverted trapezoid. An insert extends from the lower end of the textured layer into the groove and engages with the groove.
[0042] Furthermore, the groove has a depth of 30 μm, and the distance between two adjacent grooves is 100 μm. The top width of the groove cross-section is 50 μm, and the bottom width is 30 μm.
[0043] Furthermore, the thickness of the textured layer is 90 μm; the thickness of the TPU foam layer is 0.5 cm.
[0044] The TPU foam film of this invention, which maintains its three-dimensional texture even after multiple hot pressings, has an ingenious structure. A groove with an inverted trapezoidal cross-section is provided on the surface of the TPU foam layer. An insert extends from the lower end of the textured layer into the groove, allowing the composite PU coating to penetrate and solidify within the groove. The groove and the insert form a "rivet"-like mechanical interlocking structure, enhancing mechanical interlocking and ensuring a stable connection between the TPU foam layer and the textured layer. This prevents delamination of the TPU foam layer and textured layer after two hot pressings during the production process. Furthermore, the three-dimensional texture of the textured layer remains unchanged and clearly discernible after multiple hot pressings. The textured layer possesses excellent adhesion, good shape retention, and excellent stability, as well as superior heat resistance and bending resistance, highlighting the three-dimensionality and clarity of the product surface.
[0045] Example 2
[0046] In this embodiment, a TPU foam film with a three-dimensional texture that does not deform after multiple hot pressings includes a textured layer, a TPU foam layer, a TPU hot melt adhesive film, and a non-woven fabric arranged sequentially from top to bottom. The textured layer is disposed on the upper surface of the TPU foam layer, and multiple grooves are formed on the upper surface of the TPU foam layer. The multiple grooves are arranged in a matrix, and the cross-section of the groove is an inverted trapezoid. An insert extends from the lower end of the textured layer into the groove and engages with the groove.
[0047] Furthermore, the groove has a depth of 30 μm, and the distance between two adjacent grooves is 100 μm. The top width of the groove cross-section is 50 μm, and the bottom width is 30 μm.
[0048] Furthermore, the thickness of the textured layer is 90 μm; the thickness of the TPU foam layer is 0.5 cm; the thickness of the TPU hot melt adhesive film is 0.08 cm; and the thickness of the nonwoven fabric is 0.2 cm.
[0049] Example 3
[0050] In this embodiment, the textured layer is coated with a composite PU coating, and the preparation method of the composite PU coating includes the following steps:
[0051] A1. Place the diol in a reaction vessel, stir and heat to 120°C, control the pressure inside the reaction vessel to -0.04 MPa, and dehydrate; then purge with nitrogen, cool to 80°C, add isophorone diisocyanate and catalyst, catalyze the reaction for 3 hours, cool to 70°C, add 1-(furan-2-yl)-neopentane-1,3-diol for chain extension reaction for 1.5 hours, then add methyl ethyl ketone oxime for end-capping reaction for 1.5 hours. Once the reaction is complete, mixture one is obtained.
[0052] A2. Raise the temperature to 75℃, add silica sol and alumina nanoparticles to mixture one, stir evenly and sonicate for 1.5h to obtain mixture two;
[0053] A3. Cool to room temperature, add bismaleimide and epoxy resin to mixture two and stir until homogeneous to obtain composite PU coating.
[0054] Furthermore, the molar ratio of the diol, 1-(furan-2-yl)-neopentane-1,3-diol, methyl ethyl ketone oxime and isophorone diisocyanate is 1:0.6:0.4:1.8.
[0055] Furthermore, the diol is polycaprolactone diol 1000.
[0056] Furthermore, the molar ratio of the bismaleimide to 1-(furan-2-yl)-neopentane-1,3-diol is 1:2.3.
[0057] Furthermore, the amount of epoxy resin added is 20% of the total mass of the diol, 1-(furan-2-yl)-neopentane-1,3-diol, methyl ethyl ketone oxime and isophorone diisocyanate.
[0058] Furthermore, the epoxy resin used is a bisphenol A type epoxy resin with an epoxy value of 0.46 from Shanghai Luohe High-Tech Materials Co., Ltd.
[0059] Furthermore, the total amount of silica sol and alumina nanoparticles added is 14% of the total mass of diol, 1-(furan-2-yl)-neopentane-1,3-diol, methyl ethyl ketone oxime and isophorone diisocyanate, and the mass ratio of silica sol to alumina nanoparticles is 1:0.6.
[0060] Furthermore, the alumina nanoparticles have a particle size of 50 nm.
[0061] Furthermore, the preparation method of the silica sol includes the following steps: tetraethyl orthosilicate, deionized water and anhydrous ethanol are mixed in a molar ratio of 1:4:4, the pH value is adjusted to 1.5 with concentrated hydrochloric acid, and the mixture is stirred at 300 r / min for 30 min at 35°C to obtain silica sol.
[0062] Furthermore, the catalyst is dibutyltin dilaurate. The amount of catalyst added is 0.04% of the total mass of the diol, 1-(furan-2-yl)-neopent-1,3-diol, methyl ethyl ketone oxime, and isophorone diisocyanate.
[0063] The present invention also provides a method for preparing a TPU foam film with non-deformable three-dimensional texture after multiple hot pressing, comprising the following steps:
[0064] S1. Take the TPU foam layer, carve grooves on the upper surface of the TPU foam layer using an ultraviolet laser engraving machine, then place it in a processing chamber and introduce nitrogen gas, and use plasma equipment to perform plasma surface activation on the upper surface of the TPU foam layer.
[0065] S2. Under nitrogen protection, the composite PU coating is applied to the upper surface of the activated TPU foam layer to form a composite PU layer. The composite PU layer is hot-pressed at 140℃ for 50 seconds using a mold and then rapidly cooled to room temperature at a pressure of 15 MPa, so that uneven textures are formed on the upper surface of the composite PU layer, forming a textured layer.
[0066] S3. Take TPU hot melt adhesive film and non-woven fabric, and attach the TPU hot melt adhesive film and non-woven fabric to the lower surface of the TPU foam layer from top to bottom. Use a mold to hot press it at 100℃ for 20 seconds and then quickly cool it to room temperature at a pressure of 0.7Mpa. This allows the TPU hot melt adhesive film to melt and firmly bond the TPU foam layer and non-woven fabric together to obtain a TPU foam film.
[0067] Furthermore, in step S1, the ultraviolet laser engraving machine uses an ultraviolet light wavelength of 355nm, the plasma processing power is 100W, the pressure is 40Pa, and the processing time is 120s.
[0068] Furthermore, the TPU foam layer uses TPU foam film of model ZD-85A from Guangdong Zhongding Technology Development Co., Ltd., with a thickness of 0.5cm and a density of 0.3g / cm³. 3 .
[0069] The rest of this embodiment is the same as that in Embodiment 2.
[0070] Example 4
[0071] In this embodiment, the preparation method of the composite PU coating includes the following steps:
[0072] A1. Place the diol in a reaction vessel, stir and heat to 120°C, control the pressure inside the reaction vessel to -0.04 MPa, and dehydrate; then purge with nitrogen, cool to 80°C, add isophorone diisocyanate and catalyst, catalyze the reaction for 3 hours, cool to 70°C, add 1-(furan-2-yl)-neopentane-1,3-diol for chain extension reaction for 1.5 hours, then add methyl ethyl ketone oxime for end-capping reaction for 1.5 hours. Once the reaction is complete, mixture one is obtained.
[0073] A2. Raise the temperature to 75℃, add silica sol and alumina nanoparticles to mixture one, stir evenly and sonicate for 1.5h to obtain mixture two;
[0074] A3. Cool to room temperature, add bismaleimide and epoxy resin to mixture two and stir until homogeneous to obtain composite PU coating.
[0075] Furthermore, the diol is polytetrahydrofuran diol 1000.
[0076] The present invention also provides a method for preparing a TPU foam film with non-deformable three-dimensional texture after multiple hot pressing, comprising the following steps:
[0077] S1. Take the TPU foam layer, carve grooves on the upper surface of the TPU foam layer using an ultraviolet laser engraving machine, then place it in a processing chamber and introduce nitrogen gas, and use plasma equipment to perform plasma surface activation on the upper surface of the TPU foam layer.
[0078] S2. Under nitrogen protection, the composite PU coating is applied to the upper surface of the activated TPU foam layer to form a composite PU layer. The composite PU layer is hot-pressed at 140℃ for 50 seconds using a mold and then rapidly cooled to room temperature at a pressure of 15 MPa, so that uneven textures are formed on the upper surface of the composite PU layer, forming a textured layer.
[0079] S3. Take TPU hot melt adhesive film and non-woven fabric, and attach the TPU hot melt adhesive film and non-woven fabric to the lower surface of the TPU foam layer from top to bottom. Use a mold to hot press it at 100℃ for 20 seconds and then quickly cool it to room temperature at a pressure of 0.7Mpa. This allows the TPU hot melt adhesive film to melt and firmly bond the TPU foam layer and non-woven fabric together to obtain a TPU foam film.
[0080] The rest of this embodiment is the same as that in Embodiment 3.
[0081] Example 5
[0082] In this embodiment, the preparation method of the composite PU coating includes the following steps:
[0083] A1. Place the diol in a reaction vessel, stir and heat to 120°C, control the pressure inside the reaction vessel to -0.04 MPa, and dehydrate; then purge with nitrogen, cool to 80°C, add isophorone diisocyanate and catalyst, catalyze the reaction for 3 hours, cool to 70°C, add 1-(furan-2-yl)-neopentane-1,3-diol for chain extension reaction for 1.5 hours, then add methyl ethyl ketone oxime for end-capping reaction for 1.5 hours. Once the reaction is complete, mixture one is obtained.
[0084] A2. Raise the temperature to 75℃, add silica sol and alumina nanoparticles to mixture one, stir evenly and sonicate for 1.5h to obtain mixture two;
[0085] A3. Cool to room temperature, add bismaleimide and epoxy resin to mixture two and stir until homogeneous to obtain composite PU coating.
[0086] Furthermore, the diol is polyoxypropylene glycol 1000.
[0087] The present invention also provides a method for preparing a TPU foam film with non-deformable three-dimensional texture after multiple hot pressing, comprising the following steps:
[0088] S1. Take the TPU foam layer, carve grooves on the upper surface of the TPU foam layer using an ultraviolet laser engraving machine, then place it in a processing chamber and introduce nitrogen gas, and use plasma equipment to perform plasma surface activation on the upper surface of the TPU foam layer.
[0089] S2. Under nitrogen protection, the composite PU coating is applied to the upper surface of the activated TPU foam layer to form a composite PU layer. The composite PU layer is hot-pressed at 140℃ for 50 seconds using a mold and then rapidly cooled to room temperature at a pressure of 15 MPa, so that uneven textures are formed on the upper surface of the composite PU layer, forming a textured layer.
[0090] S3. Take TPU hot melt adhesive film and non-woven fabric, and attach the TPU hot melt adhesive film and non-woven fabric to the lower surface of the TPU foam layer from top to bottom. Use a mold to hot press it at 100℃ for 20 seconds and then quickly cool it to room temperature at a pressure of 0.7Mpa. This allows the TPU hot melt adhesive film to melt and firmly bond the TPU foam layer and non-woven fabric together to obtain a TPU foam film.
[0091] The rest of this embodiment is the same as that in Embodiment 3.
[0092] Comparative Example 1
[0093] The difference between this comparative example and Example 3 is that epoxy resin is not added in the preparation method of the composite PU coating.
[0094] Comparative Example 2
[0095] The difference between this comparative example and Example 3 is that in the preparation method of the composite PU coating, an equal amount of silica is used to replace the silica sol, wherein the particle size of the silica is 60nm.
[0096] Comparative Example 3
[0097] The difference between this comparative example and Example 3 is that, in the preparation method of the composite PU coating, an equal amount of silica sol is used to replace alumina nanoparticles.
[0098] Performance testing
[0099] Performance tests were conducted on the TPU foam films prepared in Example 2 and Comparative Examples 1-2 that did not deform after multiple hot pressing. The abrasion resistance of the textured layer, its adhesion to the TPU foam surface under different conditions, and its heat resistance were tested. The test data are shown in Table 1 below:
[0100] Table 1
[0101]
[0102]
[0103] Among them, the abrasion resistance test: the TPU foam film was cut into the shape specified in GB / T1768-2006 and placed on the TABER abrasion resistance tester (GT-7012-T) to observe the changes in the textured layer surface. The grinding wheel type was CS-10, the speed was set to 72r / min, and the surface load weight was 1000g. The exposed bottom in Table 1 refers to the exposed bottom surface, that is, the textured layer is worn and the TPU foam layer is visible.
[0104] The adhesion test shall be conducted in accordance with GB / T9286-1998;
[0105] The aging resistance test was performed using QUV 340nm treatment for 1000 hours at a light intensity of 0.8W / cm². 2 ;
[0106] The heat resistance test was conducted according to ISO 25178. After the textured layer was hot-pressed at 100℃ for 3 minutes five times, the texture height deviation was observed using a laser confocal microscope.
[0107] The above embodiments are preferred implementations of the present invention. In addition, the present invention can be implemented in other ways. Any obvious substitutions without departing from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A TPU foam film whose three-dimensional texture does not deform after multiple hot pressings, characterized in that: It includes a textured layer and a TPU foam layer. The textured layer is disposed on the upper surface of the TPU foam layer. The upper surface of the TPU foam layer has multiple grooves arranged in a matrix. The cross-section of the grooves is an inverted trapezoid. The lower end of the textured layer extends into the grooves with an insert block that engages with the grooves. The textured layer is coated with a composite PU coating, and the preparation method of the composite PU coating includes the following steps: A1. Place the diol in a reaction vessel, stir and heat to 115-130℃, control the pressure in the reaction vessel to -0.02-0.06MPa, and dehydrate; then purge with nitrogen, cool to 75-85℃, add isophorone diisocyanate and catalyst, catalyze the reaction for 1-3 hours, cool to 65-75℃, add 1-(furan-2-yl)-neopentane-1,3-diol for chain extension reaction for 1-2 hours, then add methyl ethyl ketone oxime for end-capping reaction for 1-2 hours. Once the reaction is complete, obtain mixture one. A2. Raise the temperature to 70-80℃, add silica sol and alumina nanoparticles to mixture one, stir evenly, and sonicate for 1-2 hours to obtain mixture two. A3. Cool to room temperature, add bismaleimide and epoxy resin to mixture two and stir until homogeneous to obtain composite PU coating.
2. The TPU foam film with non-deformable three-dimensional texture after multiple hot pressings according to claim 1, characterized in that: The groove has a depth of 25-35 μm, and the distance between two adjacent grooves is 95-105 μm.
3. The TPU foam film with non-deformable three-dimensional texture after multiple hot pressings according to claim 1, characterized in that: The molar ratio of the diol, 1-(furan-2-yl)-neopentane-1,3-diol, methyl ethyl ketone oxime and isophorone diisocyanate is 1:0.4-0.8:0.2-0.6:1-2.
4. The TPU foam film with non-deformable three-dimensional texture after multiple hot pressings as described in claim 1, characterized in that: The molar ratio of the bismaleimide to 1-(furan-2-yl)-neopentane-1,3-diol is 1:2.2-2.
5.
5. The TPU foam film with non-deformable three-dimensional texture after multiple hot pressings according to claim 1, characterized in that: The amount of epoxy resin added is 15-25% of the total mass of the diol, 1-(furan-2-yl)-neopentane-1,3-diol, methyl ethyl ketone oxime and isophorone diisocyanate.
6. The TPU foam film with non-deformable three-dimensional texture after multiple hot pressings according to claim 1, characterized in that: The total amount of silica sol and alumina nanoparticles added is 8-16% of the total mass of diol, 1-(furan-2-yl)-neopentane-1,3-diol, methyl ethyl ketone oxime and isophorone diisocyanate, and the mass ratio of silica sol to alumina nanoparticles is 1:0.3-0.
7.
7. The TPU foam film with non-deformable three-dimensional texture after multiple hot pressings according to claim 1, characterized in that: The diol is at least one of polycaprolactone diol, polytetrahydrofuran diol, and polyoxypropylene diol.
8. The TPU foam film with non-deformable three-dimensional texture after multiple hot pressings according to claim 1, characterized in that: The catalyst is at least one of dibutyltin dilaurate and stannous octoate.
9. A method for preparing a TPU foam film with a three-dimensional texture that does not deform after multiple hot pressings as described in any one of claims 1-8, characterized in that: Includes the following steps: S1. Take the TPU foam layer, carve grooves on the upper surface of the TPU foam layer using an ultraviolet laser engraving machine, then put it into the processing chamber and introduce nitrogen gas, and use plasma equipment to perform plasma surface activation on the upper surface of the TPU foam layer. S2. Under nitrogen protection, the composite PU coating is applied to the upper surface of the activated TPU foam layer to form a composite PU layer. The composite PU layer is hot-pressed at a temperature of 130-150℃ for 30-60 seconds using a mold and then rapidly cooled to room temperature at a pressure of 12-17 MPa, so that an uneven texture is formed on the upper surface of the composite PU layer, forming a textured layer. S3. Take TPU hot melt adhesive film and non-woven fabric, and attach the TPU hot melt adhesive film and non-woven fabric to the lower surface of the TPU foam layer from top to bottom. Use a mold to hot press it at a temperature of 90-110℃ for 10-30 seconds, and then quickly cool it to room temperature at a pressure of 0.5-1Mpa. This allows the TPU hot melt adhesive film to melt and firmly bond the TPU foam layer and non-woven fabric together to obtain a TPU foam film.
Citation Information
Patent Citations
Method of producing resin layer having pattern
JP2015032775A
KR20230036488A
